Rethinking Value Creation in Brick-and-Mortar Retailing - David Finken; Thomas Scheurer (Marketing Review St.Gallen, 2022)
Augmented reality (AR) is coming of age. Yet it remains unclear how AR will provide value to brick-and-mortar customers and firms. Based on 12 expert interviews, this article outlines how AR can facilitate value creation for brick-and-mortar customer journeys. Managers should be aware of such potentials but also anticipate related obstacles.
Keywords: 650